Development of benzo[1,4]oxazines as biofilm inhibitors and dispersal agents against Vibrio cholerae - Warner, Christopher J. A. (Royal Society of Chemistry, 2015)

(untitled) (Chem Commun (Camb))
Bacterial biofilms are estimated to be associated with over 65 percent of all nosocomial infections. However, no therapeutics have been approved by the FDA which directly mediate biofilm formation or persistence. Herein we report oxazine 25 as a highly potent inhibitor, disperser and in the presence of the appropriate antibiotic eradicator of V. cholerae biofilms.